Pengaruh Profitabilitas dan Biaya Hutang terhadap Penghindaran Pajak Perusahaan Sub Sektor Perdagangan Besar yang Terdaftar di BEI Periode 2018–2021 - Nur Okta Qomari Kiasati; Putri Awalina; Muhammad Alfa Niam (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study was conducted to determine the effect of profitability and cost of debt on tax avoidance in wholesale trading companies from 2018 to 2021. The population in this study was 53 companies spanning a four-year period. The sample size used in this study was 49 from a population of 212. The sampling technique used was non-random sampling, with criteria being determined for sample selection. Testing was conducted using descriptive statistics, classical assumption tests, outlier tests, and multiple linear regression. The results showed that profitability and cost of debt had a significant positive effect on tax avoidance, accounting for 19.3% of the total, with the remainder coming from other variables. Partially, profitability had a significant negative effect on tax avoidance, meaning that an increase in profitability would decrease tax avoidance. Meanwhile, the cost of debt had an insignificant negative effect on tax avoidance, meaning that the higher the cost of debt, the higher the tax avoidance